2020
DOI: 10.1371/journal.pcbi.1008461
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TMPRSS2 and Cathepsin B/L together may be synergistic against SARS-CoV-2 infection

Abstract: The entry of SARS-CoV-2 into target cells requires the activation of its surface spike protein, S, by host proteases. The host serine protease TMPRSS2 and cysteine proteases Cathepsin B/L can activate S, making two independent entry pathways accessible to SARS-CoV-2. Blocking the proteases prevents SARS-CoV-2 entry in vitro. This blockade may be achieved in vivo through ‘repurposing’ drugs, a potential treatment option for COVID-19 that is now in clinical trials. Here, we found, surprisingly, that drugs target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 84 publications
(210 reference statements)
4
88
0
Order By: Relevance
“…In addition, a variety of other molecules have been suggested to be involved in the SARS-CoV-2 internalization into the host cell. Some of them are ADAM17 [ 23 ], DPP4 [ 25 ], AGTR2 [ 27 ], BSG [ 19 ], ANPEP [ 30 ], and cathepsin B/L [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a variety of other molecules have been suggested to be involved in the SARS-CoV-2 internalization into the host cell. Some of them are ADAM17 [ 23 ], DPP4 [ 25 ], AGTR2 [ 27 ], BSG [ 19 ], ANPEP [ 30 ], and cathepsin B/L [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once attached, the host infection requires the expression of transmembrane serine protease 2 (TMPRSS2) for priming of the spike protein and viral entry into the cell [ 20 22 ]. Along with ACE2 and TMPRSS2, several other molecules have been suggested to participate in SARS-CoV-2 entry into human cells, such as ADAM metallopeptidase domain 17 (ADAM17) [ 23 , 24 ], dipeptidyl peptidase 4 (DPP4) [ 25 , 26 ], angiotensin II receptor type 2 (AGTR2) [ 27 , 28 ], basigin (BSG, also called extracellular matrix metalloproteinase inducer [EMMPRIN] or cluster of differentiation 147 [CD147]) [ 19 , 29 ], aminopeptidase N (ANPEP), [ 30 ], and cathepsin B/L [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies using mathematical models that can explain SARS-CoV-2 infection dynamics and give insight into treatment strategy ( 29 , 42 , 43 , 44 ). Another mathematical study of nasal viral load also showed a longer duration of virus shedding under RDV treatment; however, that study did not directly estimate treatment efficacy ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teicoplanin is an antibacterial drug that is already in clinical use, and it may also block SARS-CoV-2 entry through the inhibition of CTSL activity [ 122 , 123 ]. Targeting TMPRSS2 and Cathepsin B/L together may be synergistic against SARS-CoV-2 infection [ 124 ].…”
Section: Therapy For Conjunctivitis Associated With Sars-cov-2mentioning
confidence: 99%